Analisis Kesalahan Penggunaan Tanda Baca dalam Teks Narasi Siswa Kelas IV SD Swasta PAB 29 Desa Manunggal Tahun Pelajaran 2024/2025 - Ashari, Tasya Aura; Siregar, Harumi (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2024)
Based on the observations made by the researcher at SD Swasta PAB 29 in Manunggal Village, it discovered that the narrative essays still include punctuation mistakes of fourth-grade students in Class IV-A at SD Swasta PAB 29, Manunggal Village. The research problem is: how are the errors in the use of periods, commas, exclamation marks, and question marks present in the narrative essays of fourth-grade students in Class IV-A at SD Swasta PAB 29, Manunggal Village? The aim of this study is to analyze and describe the errors in punctuation usage in the students' narrative essays. This is a qualitative study, and the subjects are the students of Class IV-A at SD Swasta PAB 29, Manunggal Village. Forcollection the data used random sampling, which is a technique of random selection. The results of this indicate that many students still make mistakes in punctuation usage. Variations in errors in the use of punctuation marks by students show this. Therefore, the researcher concluded that class IV-A students still had not mastered the use of punctuation marks in their essays.